Hubungan Antara Kecerdasan Emosi Dengan Forgiveness Pada Santriwati Nurul Qur'an Patokan Kraksaan Probolinggo - Faiqotul Jannah; Fuadatul Huroniyah (Fakultas Dakwah UIN KHAS Jember, 2025)
The aim of this research is to determine whether there is a relationship between emotional intelligence and resilience in female students at the Nurul Qur'an Kraksaan Islamic Boarding School, Probolinggo. In this research there are two variables, namely forgiveness and emotional intelligence. This research uses a quantitative approach with a correlational research type. The sampling technique used purposive sampling with a total of 43 subjects. The data collection technique uses questionnaires. The data in this research was obtained using the emotional intelligence scale and forgiveness scale. The results of this research show that there is a significant relationship between emotional intelligence and forgiveness in female students at the Nurul Quran Islamic boarding school. Hypothesis testing in this study used Pearson product moment correlation analysis which showed a significance value of 0.000 <0.05 and a correlation coefficient of 0.589 which indicated a positive and quite strong relationship. The higher the female students' emotional intelligence, the higher their ability to forgive. On the other hand, the lower the female students' level of emotional intelligence, the lower their ability to forgive.